Isolation and antibiotic susceptibility of bacteria from foot infections in the patients with diabetes mellitus type I and type II in the district of Kancheepuram, Tamil Nadu, India - Iyanar, Kannan; K., Premavathy R.; Cecilia, Sambandam; M., Jayalakshmi; S., Sruthi Priyadarsini; S., Shantha (International Journal of Research in Medical Sciences, 2017)
Background:Diabetic foot infections are important cause of morbidity and mortality among persons with diabetes mellitus. The reported prevalence rates in India range from 0.9–8.3%. Diabetes foot lesions are the leading cause of non-traumatic amputations worldwide. A study has been conducted to isolate and find the antibiotic susceptibility pattern of the bacteria from diabetic foot infections from the patients of Kancheepuram district, Tamil Nadu, India. Methods:Sixty patients previously diagnosed or newly diagnosed as diabetic, presented with lower extremity infection attending Tagore medical college and hospital and its peripheral centres were selected for the study. Various specimens (pus, wound exudates, or tissues biopsy) for microbiological studies were obtained from the infected region. The specimens were cultured on blood agar and MacConkey agar for aerobic / facultative anaerobic organisms and on Neomycin Blood Agar for anaerobic organism. The plates were then incubated at 37°C. For anaerobic culture the plates were incubated in the McIntosh anaerobic jar. Isolates obtained are identified by standard laboratory techniques. Results:The result showed that Pseudomonas aeruginosa (48.3%) is the predominant bacterium followed by Staphylococcus aureus (38%) and other bacteria. The anaerobic bacteria are also isolated from the diabetic foot ulcers. The Peptostreptococcus species (26.7%) are the predominant bacteria followed by other bacteria. Further the results showed that 22 patients (37%) showed the multi-bacterial infection and remaining 38 patients (63%) showed mono bacterial infection. The drugs like amikacin, cefepine, ciprofloxacin, cotrimoxazole and roxythromycin are sensitive to many gram positive bacterial isolates. Conclusion:The present study has given the data of various bacteria encountered in the diabetic foot ulcer in the district of Kancheepuram, Tamil Nadu, India and its antibiotic sensitivity pattern. The results clearly reveal that there is no definite aetiology in diabetic foot infections. Many patients presented the infection with the involvement of many bacteria. Further it is evident that many bacteria are multi drug resistant and thus complicating the management of diabetic foot infections.